2013
DOI: 10.1098/rstb.2012.0485
|View full text |Cite
|
Sign up to set email alerts
|

Pan-Arctic modelling of net ecosystem exchange of CO 2

Abstract: Net ecosystem exchange (NEE) of C varies greatly among Arctic ecosystems. Here, we show that approximately 75 per cent of this variation can be accounted for in a single regression model that predicts NEE as a function of leaf area index (LAI), air temperature and photosynthetically active radiation (PAR). The model was developed in concert with a survey of the light response of NEE in Arctic and subarctic tundras in Alaska, Greenland, Svalbard and Sweden. Model parametrizations based on data collected in one … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
74
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(83 citation statements)
references
References 32 publications
(76 reference statements)
8
74
0
Order By: Relevance
“…A. Walker et al, 2003), and fire regimes (Higuera et al, 2008), as well as wildlife habitat and trophic and by definition prohibits repeat monitoring necessary to detect change (Mascaro, Asner, Davies, Dehgan, & Saatchi, 2014). Consequently, satellite-based optical remote sensing techniques that rely on spectral vegetation indices such as the normalized difference vegetation index (NDVI; Tucker, 1979) are frequently used in the Arctic tundra to estimate biomass (Boelman et al, 2003;Simms & Ward, 2013;Donald A Walker, Auerbach, & Shippert, 1995) and other plant community characteristics such as community structure (e.g., Boelman, Gough, McLaren, & Greaves, 2011) and ecosystem carbon storage and fluxes (e.g., Shaver et al, 2013;Street, Shaver, Williams, & Van Wijk, 2007). These studies have been useful for understanding multiyear trends in the greening or browning of the arctic; however, using satellite-derived passive remote sensing techniques can be problematic because such indices can be strongly affected by factors like canopy architecture, viewing geometry, and the mixing of reflectance signals from plant leaves, woody stems, background soil, and surface water (Boelman, Stieglitz, Griffin, & Shaver, 2005;Gamon, Huemmrich, Stone, & Tweedie, 2013;Jackson & Huete, 1991;Jacquemoud & Baret, 1990;Verhoef, 1984).…”
Section: Introductionmentioning
confidence: 99%
“…A. Walker et al, 2003), and fire regimes (Higuera et al, 2008), as well as wildlife habitat and trophic and by definition prohibits repeat monitoring necessary to detect change (Mascaro, Asner, Davies, Dehgan, & Saatchi, 2014). Consequently, satellite-based optical remote sensing techniques that rely on spectral vegetation indices such as the normalized difference vegetation index (NDVI; Tucker, 1979) are frequently used in the Arctic tundra to estimate biomass (Boelman et al, 2003;Simms & Ward, 2013;Donald A Walker, Auerbach, & Shippert, 1995) and other plant community characteristics such as community structure (e.g., Boelman, Gough, McLaren, & Greaves, 2011) and ecosystem carbon storage and fluxes (e.g., Shaver et al, 2013;Street, Shaver, Williams, & Van Wijk, 2007). These studies have been useful for understanding multiyear trends in the greening or browning of the arctic; however, using satellite-derived passive remote sensing techniques can be problematic because such indices can be strongly affected by factors like canopy architecture, viewing geometry, and the mixing of reflectance signals from plant leaves, woody stems, background soil, and surface water (Boelman, Stieglitz, Griffin, & Shaver, 2005;Gamon, Huemmrich, Stone, & Tweedie, 2013;Jackson & Huete, 1991;Jacquemoud & Baret, 1990;Verhoef, 1984).…”
Section: Introductionmentioning
confidence: 99%
“…Forest floor GPP may then be estimated for each location by adding mean R to NEE at a particular level of PAR. For each location and time period, we fit a three-parameter decay model to the relationship between PAR and measured forest floor NEE by minimizing the root mean square error between observed and predicted NEE values using Excel solver (Shaver et al, 2013):…”
Section: Sampling and Data Analysesmentioning
confidence: 99%
“…Simultaneously, recent successes in generating site-level, data-driven estimates of net ecosystem CO 2 exchange (NEE) at Arctic sites (e.g., Shaver et al, 2007Shaver et al, , 2013Stoy et al, 2009), with little intersite variability in parameters (Loranty et al, 2011), have indicated the tremendous potential that exists for accurate estimates of regional-scale Arctic NEE to be modeled diagnostically from satellite observations.…”
Section: Introductionmentioning
confidence: 99%